Man’s Attitude Towards Nature and Animal Respect Questionnaire (AniRe-Que) - Kaliský, Ján; Kaliská, Lada (Studia Ecologiae et Bioethicae, 2020)
The psychometric properties of the author´s original tool named Questionnaire of the Relations between a Man and Animals (further on AniRe-Que) was constructed to assess the relations between a man and animals as natural beings; calculated in the form of an R-score (R as respect). The questionnaire is based on the theoretical outcomes of an egalitarian zoocentric, ecoethical position attributing moral statues to all beings, and measures the level of respect expression to nonhuman beings. The aim of this study was to verify its validity and reliability in a research sample of future primary and secondary teachers (N = 500, 62% of females, Mage=22.3; SD=4.1) at Matej Bel University in Banská Bystrica, Slovakia. Various statistical procedures were used to verify its construct validity (exploratory factor analysis /EFA/) and its convergent/discriminating character, criterion validity, and reliability (test-retest, parallel-forms, internal consistency) to establish satisfactory psychometric properties for the AniRe-Que questionnaire. The questionnaire has possible usage for the animal relation estimation by researchers, practitioners and teachers´ ethical and environmental education intervention effectivitiveness, and also as a form of future international cooperation and verification based on this new instrument.